2013
DOI: 10.4236/ojog.2013.39116
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral tubal pregnancy: A diagnostic dilemma

Abstract: Bilateral tubal ectopic pregnancy is very rare and usually occurs following ovulation stimulation. Moreover preoperative diagnosis is very difficult. We are presenting a case of bilateral tubal ectopic pregnancy occurring spontaneously. Hence careful follow-up with combination of color Doppler and serum beta HCG estimation of patients after laparoscopic or open surgery for ectopic pregnancies is needed to avoid such unusual event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 3 publications
(2 reference statements)
0
8
0
Order By: Relevance
“…Simultaneous rupture of tubes is even rarer. Twin tubal pregnancy with both embryos in the same tube as well as with one in each tube has also been stated [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneous rupture of tubes is even rarer. Twin tubal pregnancy with both embryos in the same tube as well as with one in each tube has also been stated [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] The diagnostic criteria for bilateral tubal pregnancy were first laid out by Fishback who suggested that there should be a description of fetal parts or fetus as well as placental parts from both the tubes. [ 7 ] This was later modified by Norris, who stated that microscopic demonstration of chorionic villi in both tubes was sufficient for the diagnosis. Thus, in most cases, the diagnosis remains essentially surgical.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] It should be included in the differential diagnosis of acute abdominal pain presenting days, or, as in some cases, weeks following treatment for a presumed singleton ectopic pregnancy. [ 7 ] The clinical presentation of bilateral ectopic pregnancy is unpredictable. [ 8 ] It bears no unique clinical features to distinguish it from a unilateral ectopic pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bilateral salpingectomy as means to manage bilateral tubal ectopic were reported in the following cases reported. 6,9,[14][15][16][17][18] Bilateral salpingostomy was performed with the goal of preserving fertility in the following cases reported. 10,12,[19][20] Salpingectomy of one tube and salpingostomy of other tube was performed in the following cases reported.…”
Section: Discussionmentioning
confidence: 99%